Beyond Sexual Assault Surveys: A Model for Comprehensive Campus Climate Assessments. Issue 1 (2nd January 2018) - McMahon, Sarah; Stepleton, Kate; Cusano, Julia; O'Connor, Julia; Gandhi, Khushbu; McGinty, Felicia
Abstract : The White House Task Force to Protect Students from Sexual Assault identified campus climate surveys as "the first step" for addressing campus sexual violence. Through a process case study, this article presents one model for engaging in a comprehensive, action-focused campus climate assessment process. Rooted in principles of community-based participatory action research, this model moves beyond the administration of a survey as a compliance tool to engage and educate the campus community about sexual violence.